Scoring Algorithm‐Based Genomic Testing in Dystonia: A Prospective Validation Study. Issue 8 (5th May 2021) - Zech, Michael; Jech, Robert; Boesch, Sylvia; Škorvánek, Matej; Necpál, Ján; Švantnerová, Jana; Wagner, Matias; Sadr‐Nabavi, Ariane; Distelmaier, Felix; Krenn, Martin; Serranová, Tereza; Rektorová, Irena; et al.
Abstract: Background: Despite the established value of genomic testing strategies, practice guidelines for their use do not exist in many indications. Objectives: We sought to validate a recently introduced scoring algorithm for dystonia, predicting the diagnostic utility of whole‐exome sequencing (WES) based on individual phenotypic aspects (age‐at‐onset, body distribution, presenting comorbidity). Methods: We prospectively enrolled a set of 209 dystonia‐affected families and obtained summary scores (0–5 points) according to the algorithm. Singleton (N = 146), duo (N = 11), and trio (N = 52) WES data were generated to identify genetic diagnoses. Results: Diagnostic yield was highest (51%) among individuals with a summary score of 5, corresponding to a manifestation of early‐onset segmental or generalized dystonia with coexisting non‐movement disorder‐related neurological symptoms. Sensitivity and specificity at the previously suggested threshold for implementation of WES (3 points) was 96% and 52%, with area under the curve of 0.81. Conclusions: The algorithm is a useful predictive tool and could be integrated into dystonia routine diagnostic protocols. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society